A Superior Contiguous Whole Genome Assembly for Shrimp (Penaeus indicus) - Katneni, Vinaya Kumar; Shekhar, Mudagandur Shashi; Jangam, Ashok Kumar; Krishnan, Karthic; Prabhudas, Sudheesh K.; Kaikkolante, Nimisha; Baghel, Dushyant Singh; Koyadan, Vijayan K.; Jena, Joykrushna; Mohapatra, Trilochan (Frontiers in Marine Science, 2022)
Penaeid shrimp fishery and culture is a commercial enterprise contributing to employment, nutritional security and foreign exchange of developing countries. The genetic improvement programs being operated in shrimp benefit hugely from genomic resources. We report here a high-quality genome assembly for a penaeid shrimp, Penaeus indicus, which is the only Crustacean assembly to meet the reference standards of 1 and 10 Mb N50 lengths for contigs and scaffolds, respectively, among genomes of >1.5 Gb assembly length. The assembly is 1.93 Gb length (34.4 Mb scaffold N50) with 28,720 protein-coding genes and 49.31% repeat elements. The P. indicus assembly has 31.99% of simple sequence repeats, the highest among sequenced animal genomes. In comparison to other shrimp genomes having short contig lengths, the P. indicus assembly has 346 un-gapped contigs of over 1 Mb length and betters other shrimp genomes on sequence contiguity. This contiguous genome revealed 15,563 coding single nucleotide polymorphisms (SNPs) of which 2,572 are non-synonymous. The assembly and the SNP data resources have applications to genetic improvement programs, evolutionary studies and stock management.